2019
DOI: 10.1111/imj.14251
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial stewardship opportunities among inpatients with diabetic foot infections: microbiology results from a tertiary hospital multidisciplinary unit

Abstract: Among 125 inpatients with diabetic foot infections managed by a multidisciplinary foot ulcer unit, knowledge of methicillin‐resistant Staphylococcus aureus colonisation status assisted decision‐making to prescribe appropriately or with‐hold empiric anti‐methicillin‐resistant Staphylococcus aureus therapy. Despite adherence to national guidelines, apparent overuse of anti‐pseudomonal therapy was frequent, providing potential antimicrobial stewardship opportunities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 16 publications
1
4
0
Order By: Relevance
“…[57] In contrast, an Australian study determined that 83% of patients received empirical antibiotic treatment that complied with national guidelines. [58] A study carried out in Poland yielding outcomes similar to our findings found that although there was good adherence to local prescribing guidelines, the guidelines themselves did not cover the most common pathogens responsible for DFU infection. [59] Only two patients had samples collected for microbiological testing and culture identification.…”
Section: Researchsupporting
confidence: 72%
“…[57] In contrast, an Australian study determined that 83% of patients received empirical antibiotic treatment that complied with national guidelines. [58] A study carried out in Poland yielding outcomes similar to our findings found that although there was good adherence to local prescribing guidelines, the guidelines themselves did not cover the most common pathogens responsible for DFU infection. [59] Only two patients had samples collected for microbiological testing and culture identification.…”
Section: Researchsupporting
confidence: 72%
“…Our findings are consistent with previous studies in the United States noting discrepancies between empiric anti-MRSA and antipseudomonal therapies and microbiologic results with these organisms. 6,11,12 In contrast, in Western Australia, Hand et al 13 found a significant difference between the frequency of empiric antipseudomonal therapy and the frequency of isolation of P. aeruginosa in microbiologic testing; however, there was no significant difference between the frequency of empiric anti-MRSA therapy and the frequency of isolation of MRSA in microbiologic testing, 12.6% versus 11.9%, respectively. Notably, Western Australia has a wellestablished screening program for patients at high risk of MRSA with positive results prompting an electronic flag in the patient's medical record.…”
Section: Discussionmentioning
confidence: 93%
“…Our study focused on the NPV of risk factors with the goal of identifying patients for whom empiric broad-spectrum therapies could be withheld. Hand et al 13 found that the positive and negative predictive values of prior infection or colonization with MRSA for the subsequent recovery of MRSA were 54% and 97%, respectively. Mergenhagen et al 5 evaluated the utility of MRSA nares screening for patients with DFI.…”
Section: Discussionmentioning
confidence: 99%
“…A survey of Australian and New Zealand vascular and orthopaedic surgeons found they had relatively similar management practices, but few were guided by best practice clinical guidelines for DFI (Seng et al 2022). An Australian study reported microbiology results from patients with DFI managed in a tertiary inpatient setting and revealed antimicrobial stewardship opportunities with overuse of antipseudomonal agents despite adherence to national antibiotic prescribing guidelines (Hand et al 2019). The utility of wound swab vs tissue sampling in patients with DFI has been investigated by the CODIFI study, which found that the most commonly reported pathogens were Staphylococcus aureus (43.8%), Streptococcus (16.7%) and other aerobic Gram-positive cocci (70.6%) and 86.1% of tissue samples reported at least one potential pathogen compared with 70.1% of wound swabs collected (Nelson et al 2018).…”
Section: Diabetes-related Foot Infections: Microbiology and Microbiomementioning
confidence: 99%